Macromolecular Ligand Engineering for Programmable Nanoprism Assembly - Liu, Yang; Klement, Marco; Wang, Yi; Zhong, Yaxu; Zhu, Baixu; Chen, Jun; Engel, Michael; Ye, Xingchen (Journal of the American Chemical Society, 2021)
Ligands play a central role for the energetics and kinetics of nanocrystal assembly. Yet, the precise and simultaneous manipulation of ligands to dictate assembly outcome has proven difficult. Here, we present macromolecular ligand-engineering strategies to control, characterize, and model four molecular parameters of grafted polymer chains: chain length, chain dispersity, grafting density, and chain distribution. Direct ligand-exchange between nanoprisms and polymers functionalizes facets selectively and produces patchy nanocrystals. We develop a generalizable two-step ligand-exchange approach for the independent control of the two emergent brush parameters, brush thickness and brush softness. The resultant polymer-grafted prismatic nanocrystals with programmable ligand brushes self-assemble into thin-film superstructures of different wallpaper symmetries and faceted supracrystals. Our experiments are complemented by coarse-grained computer simulations of nanoprisms with directional, facet-specific interactions. This work paves the way for the precision synthesis of polymer-nanocrystal hybrid materials and enables the further refinement of theoretical models for particle brush materials.
CRIS-Team Scopus Importer:2021-10-22